Correlation between TNF-α -308 and +489 Gene Polymorphism and Acute Exacerbation of Chronic Obstructive Pulmonary Diseases. (2nd March 2021) - Yu, Suyun; Xue, Min; Yan, Zhijun; Song, Bin; Hong, Haiping; Gao, Xiwen
Abstract : Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is becoming a common respiratory disease, leading to increased morbidity and mortality worldwide. Tumor necrosis factor-alpha (TNF- α ) is a powerful proinflammatory cytokine involved in the pathogenesis of AECOPD. Therefore, we proposed a close correlation between the TNF- α polymorphism [-308G/A (rs1800629), +489G/A (rs1800610)] and the disease progress of patients with AECOPD. Comparison of the TNF- α genotypes between the 198 AECOPD diagnosed patients groups and 195 healthy peoples suggested their significant differences of the three genotypes (AA, GA, GG) distribution for TNF- α -308 (P < 0.05 ), but no differences of that for TNF- α +489. We found that patients with TNF- α -308 GA/AA genotypes showed smaller adjacent arterial diameter, thicker bronchial wall, higher bronchial artery ratio, higher bronchial wall grading, and higher frequency of acute exacerbations than those with TNF- α -308 GG genotype. Patients with TNF- α +489 GA/AA genotypes showed the same AECOPD properties as patients with TNF- α -308 except for the high frequency of acute exacerbations. Further experiment showed that the TNF- α -308 and+489 gene polymorphisms could affect the expression level of TNF- α in macrophages, suggesting the involvement of the macrophage population in disease regulation of AECOPD patients with TNF- α -308G/A and+489G/A genotype heterogeneity. In conclusion, the TNF- α -308 G/A genotype was related to AECOPD susceptibility and progress, while the TNF- α +489G/A genotype was related to AECOPD progress, but not AECOPD susceptibility.